Revitalisasi Pembelajaran PAI Untuk Membangun Kemandirian dan Tanggung Jawab Siswa - Julya Putri, Fadillah; Az Zahra, Qonita; Neni (Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe revitalization strategies for Islamic Religious Education (PAI) learning in fostering students’ independence and responsibility in the era of modern education. Using a descriptive qualitative approach through a literature study, this research examines Self-Determination Theory, Vygotsky’s social constructivism, and Kohlberg’s moral development theory as the analytical foundation. Data were analyzed through reduction, presentation, and conclusion drawing based on content analysis. The findings show that revitalizing PAI requires a contextual and integrative curriculum, active–reflective learning methods, the use of digital technology, and the strengthening of the teacher’s role as a facilitator of values and a character mentor. The results indicate that such revitalization can enhance learners’ autonomy, intrinsic motivation, and moral and social responsibility. In addition, a shift in classroom culture toward a more participatory environment further reinforces character formation. However, implementation still faces challenges, including teacher competency, limited facilities, and cultural resistance. The study concludes that revitalizing PAI is a strategic and sustainable effort in shaping a generation that is independent, ethical, and responsible